PENGARUH COMMUNICATION, JOB SATISFACTION, DANORGANIZATIONAL COMMITMENT TERHADAP SERVICE QUALITY PADA KARYAWAN BANK SYARIAH INDONESIA JAKARTA PUSAT - Amalia Rosdiana; Netania Emilisa; Tiara Puspa; Bunga Barleana Hapsari; Fitriyani (Media Riset Bisnis & Manajemen, 2024)
This research was to analyze the impact of communication, job satisfaction, and organizational commitment to service quality of employees of Islamic banking institutions in Central Jakarta. The primary data was obtained using questionnaire of 113 employees, Data analysis was performed using SEM. This research indicated that all hypotheses are accepted. Communication and job satisfaction have a positive and significant effect on organizational commitment. Organizational commitment also shows a positive and significant effect on service quality. Furthermore, organizational commitment mediates the effect of communication and job satisfaction on service quality. These findings suggest that communication and job satisfaction can influence service quality through organizational commitment. This study is focused on evaluating the mediating role of organizational commitment in the relationship between communication and job satisfaction on service quality among employees of an Islamic banking institution, specifically at one branch office and the head office located in Central Jakarta. This research examines three main variables: communication, job satisfaction, and organizational commitment, as well as one dependent variable, namely service quality.